Anthropogenic Drought: Definition, Challenges, and Opportunities. (20th April 2021) - AghaKouchak, Amir; Mirchi, Ali; Madani, Kaveh; Di Baldassarre, Giuliano; Nazemi, Ali; Alborzi, Aneseh; Anjileli, Hassan; Azarderakhsh, Marzi; Chiang, Felicia; Hassanzadeh, Elmira; Huning, Laurie S.; Mallakpour, Iman; et al.
Abstract: Traditional, mainstream definitions of drought describe it as deficit in water‐related variables or water‐dependent activities (e.g., precipitation, soil moisture, surface and groundwater storage, and irrigation) due to natural variabilities that are out of the control of local decision‐makers. Here, we argue that within coupled human‐water systems, drought must be defined and understood as a process as opposed to a product to help better frame and describe the complex and interrelated dynamics of both natural and human‐induced changes that define anthropogenic drought as a compound multidimensional and multiscale phenomenon, governed by the combination of natural water variability, climate change, human decisions and activities, and altered micro‐climate conditions due to changes in land and water management. This definition considers the full spectrum of dynamic feedbacks and processes (e.g., land‐atmosphere interactions and water and energy balance) within human‐nature systems that drive the development of anthropogenic drought . This process magnifies the water supply demand gap and can lead to water bankruptcy, which will become more rampant around the globe in the coming decades due to continuously growing water demands under compounding effects of climate change and global environmental degradation. This challenge has de facto implications for both short‐term and long‐term water resources planning and management, water governance, and policymaking. Herein, after a brief overview of the anthropogenic drought concept and its examples, we discuss existing research gaps and opportunities for better understanding, modeling, and management of this phenomenon. Plain Language Summary: This article reviews research and progress on the notion of anthropogenic drought broadly defined as drought events caused or intensified by human activities. Most commonly used drought definitions are based on deficit in hydrologic/meteorologic drivers such as precipitation and runoff. Within coupled human‐water systems, however, drought must be defined and understood as the complex and interrelated dynamics of both natural and human‐induced changes. This anthropogenic drought definition considers the full spectrum of dynamic feedbacks and processes (e.g., land‐atmosphere interactions and water and energy balance) within human‐nature systems. Ideally, anthropogenic drought and the corresponding human interactions should be incorporated in models that include land‐atmosphere interactions, water balance, and energy balance. In this article, we review existing research gaps and opportunities for better understanding, modeling, and management of this phenomenon. Key Points: Anthropogenic drought is primarily governed by the joint impacts of natural renewable water variability, climate change, and human decisions Anthropogenic drought and water bankruptcy will become more ubiquitous under current development and climate change trajectories Ideally, human interactions should be incorporated in models that include land‐atmosphere interactions, water balance and energy balance